Perfil de autocuidado de servidores com diabetes e hipertensão autorreferida que atuam em uma instituição de ensino superior pública no estado do Amazonas - Bitar, Anna Camilly Oliveira (Brasil, 2024)
Introduction: Non-communicable chronic diseases have shown significant growth worldwide. Diabetes Mellitus and Arterial Hypertension are recognized as worsening quality of life and require self-care by affected individuals. General Objective: To analyze the lifestyle and presence of common mental disorders among employees working at a university in Amazonas, as well as the quality of life and self-care of those with Diabetes and self-reported Hypertension. Specific Objectives: Characterize the sociodemographic, work-related, and personal health conditions of employees from academic units in the capital and interior. Determine differences in lifestyle and presence of common mental disorders between the groups. Identify the prevalence of self-reported diabetes and hypertension, as well as the self-care profile and quality of life of participants who reported having at least one of these morbidities. Method: Descriptive, cross-sectional study conducted with public servants of a university. Data collection was done through an online instrument, with results presented in tables. Results: Among the total participants (86), the majority were female (75%), with a mean age of 42 (±9.2) years and affiliated with academic units in the state capital (65.1%). The prevalence of self-reported hypertension and diabetes was 17.4% and 7%, respectively. Family income above 10 minimum wages and professional experience of more than 11 years were more frequent among workers in the capital (30.4% and 51.8%). The most used means of transportation for both groups was car/motorcycle (90.7%). Almost half of the participants from the capital reported no worsening of habits in the last 2 years (44.7%), while worsening of sleep and rest was more frequent among participants from the interior (53.3%). Screening for Common Mental Disorders revealed that men reported more sleep problems, while women reported more indigestion and difficulty making decisions. The quality of life of hypertensive participants was considered good, with positive average scores in the Mental State and Somatic Manifestations domains. However, a deficit in self-care was identified in the Maintenance Dimension. Among participants with diabetes, half had poor perception of Quality of Life in the Satisfaction domain. Self-care analysis showed high scores in the Maintenance and Confidence dimensions and low scores in Monitoring and Self-care Management. Conclusion: The results evidenced a good perception of quality of life in hypertension but suboptimal self-care, similarly, the quality of life in diabetes did not show positive results, however, these participants presented promising results in areas of self-care. Therefore, interventions focusing on health promotion and well-being, with participative involvement of the workers, are strategies that can favor greater adherence to good self-care practices, supporting especially those with chronic diseases, such as hypertension and diabetes.